Deformation properties of arched glass fiber reinforced plastics structure under static load: Considering the soil cover and rise-span ratio. Issue 6 (April 2022) - Liu, Shu-Yan; Zhang, Zhao-Yang; Xue, Xiao; Wang, Qing-Zhou; Xiao, Cheng-Zhi
In this study, the load level, soil cover height, rise-span ratio, and arch foot constraint state were utilized to explore the mechanical properties of buried arch glass fiber reinforced plastics (GFRP) structures. Through the indoor scale-down test, the stress and deformation of arched GFRP structures under different load and soil cover height were investigated. Additionally, through the three-dimensional finite element method, the influence of the rise-span ratio and the constraint state of arch foot on the mechanical properties were obtained. The results indicate the new buried composite arch structure has excellent bearing capacity for the possible traffic load. Simultaneously, the semi-elliptical arch structure was believed to outperform the semi-circular arch structure when considering the external load. Specifically, increasing the soil cover height and reducing rise-span ratio were found to achieve the load-reduction effect.